Analisis Yuridis Terhadap Penerapan Restorative Justice Pada Pencurian di Siang Hari Dengan Kerugian di Bawah Dua Juta Lima Ratus Ribu Rupiah Berdasarkan Sema Nomor 2 Tahun 2012 - Azhari, Moh Tohri; Setiawan, Puguh Aji Hari; H, Hartana (Media Hukum Indonesia (MHI), 2025)
The criminal act of theft is one of the most frequent forms of conventional crime in Indonesia. The phenomenon of burglaries committed in broad daylight suggests its own complexity. This study aims to examine legally the normative form of criminal accountability towards burglary offenders who act in broad daylight, as well as analyze the effectiveness of the law enforcement system. The method used is the normative juridical approach method with an analytical descriptive specification. The data sources in this study include primary legal materials in the form of legislative regulations and jurisprudence, as well as secondary legal materials from relevant scientific literature. The results of the study show that although Article 362 of the Penal Code does not explicitly distinguish the time of occurrence of theft as a criminal element, thefts committed in broad daylight often illustrate a maturely planned intention by the perpetrator. In practice, law enforcement almost certainly faces constraints in proving elements of malicious intent, identification of perpetrators, as well as limitations of technical and juridical means. Therefore, forms of criminal accountability cannot simply be repressive in nature, but must be complemented by adaptive and humanistic criminal policies. Approaches such as restorative justice, community participation, as well as technology optimization in evidence need to be developed in order to create a responsive and sustainable legal system.